SOCIAL ENTREPRENEURSHIP ORIENTATION, SOCIAL INNOVATION, AND SOCIAL ENTERPRISE PERFORMANCE: THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE - Rahmi Alfina; Yesi Mutia Basri; Poppy Nurmayanti; Emrinaldi Nur Dp; Novita Indrawati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This research aims to examine the effects of social entrepreneurship orientation and social innovation on social enterprise performance by considering the mediating role of competitive advantage. Unlike previous studies that primarily focus on entrepreneurial orientation, this study integrates social entrepreneurship orientation and social innovation within a single framework to explain the performance of social enterprises. The research was conducted on cooperatives in Indragiri Hilir Regency, Riau, Indonesia, which represent one of the most prominent forms of social enterprise in the country. Data were collected through structured questionnaires distributed directly and via Google Forms, resulting in 150 valid responses from cooperative chairpersons, secretaries, and treasurers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that social entrepreneurship orientation and social innovation have significant positive effects on social enterprise performance. Furthermore, competitive advantage significantly mediates the relationships between both antecedent variables and performance. These findings extend the Resource-Based View by demonstrating that competitive advantage acts as a strategic mechanism through which social entrepreneurial capabilities are translated into superior organizational outcomes. Practically, the results provide guidance for cooperative managers and policymakers to strengthen innovation and entrepreneurial orientation in order to achieve sustainable social and economic performance.